2008
DOI: 10.1080/15368370802118662
|View full text |Cite
|
Sign up to set email alerts
|

4 Hz Magnetic Field Decreases Oxidative Stress in Mouse Brain: A Chemiluminescence Study

Abstract: We investigated the effects of delta and theta brain wave frequency magnetic fields (3, 4, and 5) on mouse brain by detecting photonic oxidative stress makers; spontaneous photon emission (SPE) and lucigenin and tert-butyl hydroperoxide (TBHP) induced chemiluminescences (CL). For this purpose, Balb/C mice were exposed to 3, 4, and 5 Hz magnetic fields (MF) at 0.7 mT for 3 h, respectively. After that we monitored SPE and lucigenin and TBHP-induced CL of the homogenates of mice brains. There was a significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…According to Liboff and Zhadin, the proposed explanation of the biological mechanism of ELF-EMF is that coupling of a variable EMF (in the range applied in this study) with a geomagnetic field (GMF) creates the conditions for an ion cyclotron resonancelike (ICR-like) effect [18,38]. Indeed, according to in vivo and in vitro studies, ELF-EMF frequencies have been demonstrated to induce various biochemical and physiological responses [10,[19][20][21][22][23][24][25][26][27][28][29] ELF-EMF frequencies were chosen for the study by considering the above findings from previous studies, and accordingly the hypotheses for SPRI and SPR2 were: SPR1:…”
Section: Study Rationale and Operating Hypothesesmentioning
confidence: 85%
See 1 more Smart Citation
“…According to Liboff and Zhadin, the proposed explanation of the biological mechanism of ELF-EMF is that coupling of a variable EMF (in the range applied in this study) with a geomagnetic field (GMF) creates the conditions for an ion cyclotron resonancelike (ICR-like) effect [18,38]. Indeed, according to in vivo and in vitro studies, ELF-EMF frequencies have been demonstrated to induce various biochemical and physiological responses [10,[19][20][21][22][23][24][25][26][27][28][29] ELF-EMF frequencies were chosen for the study by considering the above findings from previous studies, and accordingly the hypotheses for SPRI and SPR2 were: SPR1:…”
Section: Study Rationale and Operating Hypothesesmentioning
confidence: 85%
“…The acute-phase response and cytokine release during this recovery phase are normal and beneficial for the body's adaptation to exercise. However, when inflammation becomes higher or persistent as a result of continuous physical-exercise effort, it can affect an athlete's performancerelated indices [19]. The rate of recovery is influenced by the immune system (e.g., IL-10, IL-6, and TNF-α) and biochemical responses (e.g., CK), as they promote the recruitment and activation of immune cells to repair damaged tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the initial interaction step, there are two plausible transduction mechanisms: electric currents inducing minor changes in the conductive tissues (unlikely for intensities < 1 G such as used in this study), and possible direct action of the MF on endogenous magnetoreception ( 63 ). As for the cascade of biological events that follow, it has been shown that ELF-EMF effects are likely to involve a number of cellular targets such as changes in intracellular Ca 2+ signaling ( 64 69 ), elements of the oxidative stress cascade ( 70 , 71 ), nitric oxide ( 72 , 73 ), G-protein receptor coupling ( 74 , 75 ), and the inflammatory response ( 76 , 77 ), to name a few. Some of these cellular targets have been identified and described in the studies conducted previously by members of this group, as well as by others in the field, revealing a candidate for the cascade of events that may ultimately give rise to the observed effects on the cellular, network and behavioral levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the diverse range of NIBS techniques, extremely low-frequency, low-intensity electromagnetic elds (ELF-EMFs) have emerged as relatively safe therapeutic options. Although ELF-EMFs do not directly induce action potentials, a growing body of evidence indicates their ability to modulate various biological events, including in ammation [12,13], oxidative stress response [14][15][16], apoptosis [17], neurogenesis [18][19][20], axon outgrowth and synaptogenesis [21], and neuron-astrocyte synchronization [22] by targeting diverse signaling pathways such as calcium signaling [17,20,[22][23][24][25], nitric oxide signaling [10,[26][27][28],…”
Section: Introductionmentioning
confidence: 99%